Fabrikasi dan Karakterisasi Sel Surya Organik Berbasis ITO/CuPc/PTCDI/Ag - Nurosyid, Fahru; Kusumandari, Kusumandari (Jurnal Fisika FLUX, 2009)
Has been fabricated and characterized an organic solar cell based onCopper phthalocyanine (CuPc) and 3, 4, 9, 10 perylenetetracarboxylic diimide(PTCDI). CuPc and PTCDI layer sandwiched between two different electrode ofITO and Ag by vacuum evaporation so solar cell structure isITO/CuPc/PTCDI/Ag. UV-Vis spectra of ITO/CuPc/PTCDI/Ag is 400 nm to 760nm which is superposition of CuPc layer and PTCDI layer. From characterizationof current density â voltage (J-V) show that current under illumination higher thandark current. The power conversion efficiency of 0.40 % under illumination 100mW/cm2 are obtained with fill factor 0.33.